PSYCHOSOCIAL WELL-BEING AS AN INDICATOR OF SOCIAL SECURITY OF PERSON AND SOCIETY - Kislyakov, Pavel Aleksandrovich (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2016)
Summarizes theoretical approaches to the definition of psychosocial well-being. It shows the relationship of psychosocial well-being, social tension, social security and social health. As the methodology of research used the environmental approach. Actualized the problem of psychosocial well-being of students in modern conditions. It shows the results of the study of subjective well-being of the students using the technique of «Scale of subjective well-being» (Perrudet-Badoux, Mendelssohn and Chiche, adaptation VM Sokolova). The findings relate to the need to include indicators of psychosocial well-being of the person in the system of corresponding psycho-pedagogical and socio-psychological support of the university.